Judaism in the Roman world : collected essays - Goodman, Martin, 1953- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums ;, 2007)
Deals with the religious lives of Jews in the Roman world from late Second Temple times to the Later Roman Empire. This book analyses a series of issues important in the development of Judaism in this period. It is useful for students of ancient Judaism and those interested in Christian origins.